2002
DOI: 10.1023/a:1023342118549
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This research was conducted to evaluate acaricidal effects of some plant essences on Varroa mites and the possibility of their usage for Varroa control. First, live Varroa mites were obtained from adult honeybees with CO2 in a newly designed apparatus. Thyme, savory, rosemary, marjoram, dillsun and lavender essences at concentrations of 2 and 1 g/100 g (w/w), caused a mite mortality rate of more than 97% and 95%, respectively. Also spearmint at 2 g/100 g was able to kill more than 97% of Varroa mites. When spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Researchers found that this compound showed a high colony-to-colony variation when it was assayed in field trials (Calderone and Spivak 1995); in addition, high brood mortality and decline in mite reproduction during laboratory evaluations have been reported (Imdorf et al 1999). In the literature, assay using lavender essential oil have showed good mite mortality (Ardeshir et al 2002) moreover, affecting mite reproduction; but it has (Imdorf et al 1999). Also, lavender, laurel and thyme essential oils were found having repellent action on Varroa mite (Imdorf et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that this compound showed a high colony-to-colony variation when it was assayed in field trials (Calderone and Spivak 1995); in addition, high brood mortality and decline in mite reproduction during laboratory evaluations have been reported (Imdorf et al 1999). In the literature, assay using lavender essential oil have showed good mite mortality (Ardeshir et al 2002) moreover, affecting mite reproduction; but it has (Imdorf et al 1999). Also, lavender, laurel and thyme essential oils were found having repellent action on Varroa mite (Imdorf et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The main experiments were done between August and October. To separate mites from infested honey bees, an instrument was designed as described by Ariana et al (2002) that had two cylinders, one inside the other. About 1000–2000 adult bees were poured into the inner cylinder and after closing the inner and outer cylinders they were exposed to C0 2 gas for 5 min with 5 l/min pressure from a gas cylinder.…”
Section: Methodsmentioning
confidence: 99%
“…Mites for this experiment were collected from a separate set of highly infested colonies using a modification of the carbon dioxide (CO 2 ) method (Ariana et al 2002). In this method, bees infested with Varroa were placed in a box with a screen bottom and put in a Rubbermaid (3.5 L TakeAlongs TM , Rubbermaid, Mississauga, ON, Canada) container.…”
Section: Collection and Inoculation Of Mitesmentioning
confidence: 99%